A Study of Customer’s Perception and Inclination towards Organised Retail Stores in Bhopal: Understanding Customer Preference and Behavior in Organised Retail Stores (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Indian organised retail sectors shopping malls has seen a radical transformation and hasty expansion since the last decade. But when we consider it market size wise it still could make only 18 of total market share (www.ibef.org). Though, it is being dominated by small and unorganized business like Mom Pop shops, Kirana shops, boutiques, traditional family stores etc. Organised retail malls shopping stores are the essential part of today’s lives of people in the present age. A paper on organised retail store centre every one of the advantages of an organised retail malls shopping stores. These are the areas that are hard-pressed in ends of the week because of liberated time with self and family. Organised retail store have influenced the customers and individuals exceptionally advantageous as they to get nearly the whole things from one same rooftop and are developed perfectly to increase footfalls of customers. The main purpose of the study concluded the customer Perception and inclination towards organised retail store in malls in Bhopal, Madhya Pradesh.